Myeloperoxidase Deficiency Inhibits Cognitive Decline in the 5XFAD Mouse Model of Alzheimer’s Disease - Volkman, Rotem; Ben-Zur, Tali; Kahana, Anat; Garty, Ben Zion; Offen, Daniel (Frontiers in Neuroscience, 2019)
Myeloperoxidase (MPO) is an enzyme expressed mostly by neutrophils and is a primary mediator of neutrophils oxidative stress response. While a profound body of evidence associates neutrophil-derived MPO in the pathogenesis of Alzheimer’s disease (AD), this role has not been assessed in an animal model of AD. Here, we produced hematologic chimerism in the 5XFAD mouse model of AD, with MPO deficient mice, resulting in 5XFAD with hematologic MPO deficiency (5XFAD-MPO KO). Behavioral examinations of 5XFAD-MPO KO showed significant superior performance in spatial learning and memory, associative learning and anxiety/risk assessment behavior, as compared to 5XFAD mice transplanted with WT cells (5XFAD-WT). Hippocampal immunohistochemical and mRNA expression analyses showed significantly reduced levels of inflammatory mediators in 5XFAD-MPO KO mice with no apparent differences in the numbers of amyloid-β plaques. In addition, immunoblotting and mRNA analyses showed significantly reduced levels of APOE in 5XFAD-MPO KO. Together, these results indicate a substantial involvement of neutrophil-derived MPO in the pathology of 5XFAD model of AD and suggest MPO as a potential therapeutic target in AD.